2015
DOI: 10.1002/iub.1406
|View full text |Cite
|
Sign up to set email alerts
|

The angiogenic responses induced by release of angiogenic proteins from tumor cell‐activated platelets are regulated by distinct molecular pathways

Abstract: There is mounting evidence that tumor angiogenesis can be regulated by platelets (Plts), which serve as major sources and delivery vehicles of many proangiogenic cytokines including transforming growth factor-b and vascular endothelial growth factor. Although considerable progress has been made in understanding the role for Plt secretion in tumor angiogenesis, very little is known about the precise mechanisms underlying cancer cell induction of Plt granule release. Here, we demonstrated that nonsmall cell lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
(66 reference statements)
1
18
0
Order By: Relevance
“…In addition to their ability to release angiogenic factors upon activation, platelets can also sequester VEGF, as evidenced by the preferential accumulation of VEGF in platelets compared to plasma or other cells after subcutaneous injection of radiolabeled VEGF into mice [ 69 , 70 ]. Wu et al, have recently demonstrated that non-small cell lung cancer (A549)-activated platelet releasate can stimulate angiogenesis even in the presence of VEGF neutralising antibody [ 71 ]. Therefore, platelet-derived VEGF contributes to tumour angiogenesis but is not essential as activated platelets can also release microvesicles and exosomes to induce expression of angiogenic factors in cancer cells [ 11 ].…”
Section: The Role Of Platelets In Tumour Angiogenesismentioning
confidence: 99%
“…In addition to their ability to release angiogenic factors upon activation, platelets can also sequester VEGF, as evidenced by the preferential accumulation of VEGF in platelets compared to plasma or other cells after subcutaneous injection of radiolabeled VEGF into mice [ 69 , 70 ]. Wu et al, have recently demonstrated that non-small cell lung cancer (A549)-activated platelet releasate can stimulate angiogenesis even in the presence of VEGF neutralising antibody [ 71 ]. Therefore, platelet-derived VEGF contributes to tumour angiogenesis but is not essential as activated platelets can also release microvesicles and exosomes to induce expression of angiogenic factors in cancer cells [ 11 ].…”
Section: The Role Of Platelets In Tumour Angiogenesismentioning
confidence: 99%
“…There is accumulating evidence indicating that platelets are activated to release pro-angiogenic factors in response to neighbor cells, including tumor cells 23, 2931 . This may account for the observed platelet-induced increases in EOMA cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al . reported that lung cancer cells could induce platelets to release several pro-angiogenic factors, including IL-1α, GM-CSF, MMP-1 and VEGF, resulting in enhanced endothelial cell migration and capillary tube formation 23 . However, when we evaluated CD62P surface levels we did not observe significant activation by EOMA cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capillary tube formation was performed as we described previously . Briefly, Matrigel was added into 24‐well plates (100 μL/well) and solidified in a 37°C incubator.…”
Section: Methodsmentioning
confidence: 99%